Protein-protein interactions in fatty acid elongase complexes are important for very-long-chain fatty acid synthesis - Kim, Juyoung (Journal of experimental botany, 2022)
© The Author(s) 2021. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.